Photoluminescence, energy transfer, and thermal stability of BaAl2Si2O8:Bi3+, Tb3+ phosphors for w-LEDs. Issue 1 (January 2017) - Ma, Pingchuan; Song, Yanhua; Yuan, Bo; Sheng, Ye; Xu, Chengyi; Zou, Haifeng; Zheng, Keyan
Abstract: A series of Tb 3+ or/and Bi 3+ doped BaAl2 Si2 O8 phosphors were synthesized via solid-state method. The structure, luminescence properties and thermal stability were investigated. The optimum concentrations of Bi 3+ and Tb 3+ were 1.5 mol% and 7 mol%, respectively. Furthermore, BaAl2 Si2 O8 :0.015Bi 3+ and BaAl2 Si2 O8 :0.07Tb 3+ phosphors emitted blue and green light and the emission color of BaAl2 Si2 O8 :Bi 3+, Tb 3+ could be tuned from blue to green through the energy transfer. This energy transfer from Bi 3+ to Tb 3+ was confirmed and investigated by photoluminescence spectrum and decay lifetime. With constantly increasing Tb 3+ concentrations, the energy transfer efficiency from Bi 3+ to Tb 3+ in BaAl2 Si2 O8 host increased gradually and reached as high as 86.54%, the quantum yield was about 44.26%. The energy transfer mechanism (Bi 3+ -Tb 3+ ) was proved to be dipole–dipole mechanism. The Tb 3+ emission intensity can be considerably enhanced when monitored at NUV (377 nm) by co-doping Bi 3+ ion. Moreover, the phosphor of BaAl2 Si2 O8 :0.015Bi 3+, 0.07Tb 3+ could exhibited strong green emission with good CIE chromaticity coordinate. The results indicate that BaAl2 Si2 O8 :Tb 3+, Bi 3+ is a potential green emitting phosphor for the application in w-LEDs.